2018
DOI: 10.1111/cen.13831
|View full text |Cite
|
Sign up to set email alerts
|

NovelNR5A1mutations found in Chinese patients with 46,XYdisorders of sex development

Abstract: Four novel mutations in the NR5A1 gene were identified in our cohort with 46, XY DSD, expanding the spectrum of NR5A1 gene mutations. All patients with NR5A1 rare variants had normal adrenal function and showed genital defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 45 publications
0
7
2
Order By: Relevance
“…Patients and methods have been described in detail previously [ 24 ]. Briefly, 60 patients with 46, XY DSD were admitted to the Endocrinology Department of Peking Union Medical College Hospital, Beijing between January 2010 and October 2015.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients and methods have been described in detail previously [ 24 ]. Briefly, 60 patients with 46, XY DSD were admitted to the Endocrinology Department of Peking Union Medical College Hospital, Beijing between January 2010 and October 2015.…”
Section: Methodsmentioning
confidence: 99%
“…Targeted next-generation sequencing and Sanger sequencing were used to identify and validate the gene mutation, respectively. The gene panel (NimblegenSeqCap EZ system, Roche, Basel, Switzerland) was designed to capture all exons and 50-bp flanking intron sequences of 83 DSD-related genes [ 24 ]. A variant was recognized as an underlying disease-causing variant when it was not found in dbSNP, ExAC, GnomAD, and Ensemble database and in 500 Chinese controls, or alternatively, when the allele frequency was found to be less than 0.001 in the database.…”
Section: Methodsmentioning
confidence: 99%
“…Bioinformatic analysis including quality control, reads alignment, and variants calling (including single-nucleotide variations [SNVs] and small indels) was performed following the pipelines previously described. 13 …”
Section: Methodsmentioning
confidence: 99%
“…The novel c.64G > T (p.G22C) mutation reported in the present study is a missense mutation, which reportedly accounts for 58% of NR5A1 mutations [6]. The p.G22C is located in the DBD, which is one of three domains in NR5A1, and previous studies have reported this as the location for multiple mutations in patients with 46, XY DSD [6, 20,23,24]. A previous study identi ed a G35E substitution in the DBD region in a patient with 46, XY DSD presenting adrenal insu ciency along with moderately severe gonadal dysplasia, indicating that this variation results in serious adverse effects on NR5A1 function [20].…”
Section: Discussionmentioning
confidence: 58%